Digital Learning in Crisis: Assessing Zenius’s Role in Sustaining Educational Quality at Madrasah Aliyah Pondok Pesantren Ali Maksum During Pandemic Era - Sabarudin, Sabarudin; Sa’diyah, Siti Halawatus; Syafii, Ahmad (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: This study investigates the adoption of the Zenius digital learning platform at Madrasah Aliyah Pondok Pesantren Ali Maksum, an Islamic boarding school in Yogyakarta, during the pandemic era pandemic. Employing a qualitative case study methodology, the research focuses on the school’s strategic use of Zenius to maintain educational quality for 12th-grade students. Methodological triangulation, encompassing interviews, observations, and document analysis, enabled an in-depth evaluation of the digital learning implementation and its impacts. Key findings indicate that Zenius, with features like ZenBot, Live Classes, and a comprehensive Content Library, effectively supported the learning process, evidenced by the UTBK (University Entrance Test) scores analysis. Despite its successful application, challenges were noted in tutors’ subject matter mastery and the need for more individualised instruction. The study’s limitations include its focus on a single institution and reliance on observational data, which may affect generalizability. The research contributes to the discourse on educational technology, highlighting the necessity for adaptable, student-centred learning environments and continuous educator training. Future research directions include broadening the scope to multiple institutions and incorporating qualitative analyses to better understand technology’s role in education during crises. This study underscores the importance of integrating innovative educational methods, particularly in challenging times, with implications for educational policy and practices. Abstrak: Penelitian ini menyelidiki adopsi platform pembelajaran digital Zenius di Madrasah Aliyah Pondok Pesantren Ali Maksum, sebuah pesantren di Yogyakarta, selama masa pandemi. Menggunakan metodologi studi kasus kualitatif, penelitian ini berfokus pada penggunaan strategis Zenius oleh sekolah untuk mempertahankan kualitas pendidikan bagi siswa kelas 12. Triangulasi metodologis, yang mencakup wawancara, observasi, dan analisis dokumen, memungkinkan evaluasi mendalam tentang implementasi pembelajaran digital dan dampaknya. Temuan utama menunjukkan bahwa Zenius, dengan fitur-fitur seperti ZenBot, Kelas Live, dan Perpustakaan Konten yang komprehensif, secara efektif mendukung proses pembelajaran, seperti yang dibuktikan oleh analisis skor UTBK (Ujian Tulis Berbasis Komputer). Meskipun aplikasi ini berhasil, tantangan tercatat dalam penguasaan materi oleh tutor dan kebutuhan akan pengajaran yang lebih individual. Keterbatasan penelitian ini termasuk fokus pada satu institusi dan ketergantungan pada data observasional, yang dapat mempengaruhi generalisasi. Penelitian ini berkontribusi pada diskusi tentang teknologi pendidikan, menyoroti pentingnya lingkungan pembelajaran yang adaptif dan berpusat pada siswa serta pelatihan terus-menerus bagi pendidik. Arah penelitian di masa depan mencakup memperluas cakupan ke beberapa institusi dan menggabungkan analisis kualitatif untuk pemahaman yang lebih mendalam tentang peran teknologi dalam pendidikan selama krisis. Studi ini menekankan pentingnya mengintegrasikan metode pendidikan inovatif, terutama di masa-masa sulit, dengan implikasi bagi kebijakan dan praktik pendidikan.